Sejarah Sosial Islam di Sambas : Studi Naskah Komite Masjid Baru di Kota Sambas Tahun 1925 - Sunandar Sunandar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study is a philological examination of one of the manuscripts owned by the Regional Museum of Sambas Regency, preserved as part of its philological collection. Manuscripts are, in essence, rich in values, serving as products of their time and recording contemporary events. These values can be understood through philological studies using appropriate methods. This research elaborates on three main aspects: the transliteration of the KMBKS manuscript, the contents of the KMBKS manuscript, and the context of Sambas at the time the manuscript was created.The study employs a qualitative descriptive method and a philological approach. The findings reveal that the KMBKS manuscript is written in Jawi script, with 40 lines per page. The manuscript is generally in good condition. It contains at least three main themes: first, exhortations; second, details of the required funds; and third, the composition of the management or Bestuur Commissie.